a) You need to substitute 0 for x in equation under limit such that:

`lim_(x-gt0)(1-cos(3x))/(1-cos(5x)) =(1-cos(0))/(1-cos(0)) = (1-1)/(1-1) = 0/0`

You should use l'Hospital's theorem such that:

`lim_(x-gt0) (1-cos(3x))/(1-cos(5x)) = lim_(x-gt0) ((1-cos(3x))')/((1-cos(5x))') `

`lim_(x-gt0) ((1-cos(3x))')/((1-cos(5x))') = lim_(x-gt0) (3sin(3x))/(5sin(5x)) = 0/0`

You need to use l'Hospital's theorem again such that:

`lim_(x-gt0) (3sin(3x))/(5sin(5x)) = lim_(x-gt0) ((3sin(3x))')/((5sin(5x)) ')`

`lim_(x-gt0) ((3sin(3x))')/((5sin(5x)) ') = lim_(x-gt0) (9cos(3x))/(25cos(5x))`

You need to substitute 0 for x in equation under limit such that:

`lim_(x-gt0) (9cos(3x))/(25cos(5x)) =(9cos(0))/(25cos(0))= 9/25`

**Hence, evaluating the limit to the function yields `lim_(x-gt0) (1-cos(3x))/(1-cos(5x)) = 9/25.` **

b) You need to substitute 1 for x in equation under limit such that:

`lim_(x-gt1)(6^x- 5^x - 1)/(x^2-1) = (6 - 5 - 1)/(1-1) = 0/0`

You should use l'Hospital's theorem such that:

`lim_(x-gt1)(6^x- 5^x - 1)/(x^2-1) =lim_(x-gt1)((6^x- 5^x - 1)')/((x^2-1)')`

`lim_(x-gt1)((6^x- 5^x - 1)')/((x^2-1)') = lim_(x-gt1)(6^xln 6- 5^xln 5)/(2x)`

You need to substitute 1 for x in equation under limit such that:

`lim_(x-gt1)(6^xln 6- 5^xln 5)/(2x) = (6ln 6- 5ln 5)/2`

**Hence, evaluating the limit to the function yields `lim_(x-gt1)(6^x- 5^x - 1)/(x^2-1) = ln sqrt (6^6/5^5).` **

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.